2019
DOI: 10.1182/blood.2019002105
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lamellipodium formation is not required for thrombus formation and stability

Abstract: Key Points Cyfip1 plays a crucial role for branching of actin filaments and for lamellipodium formation. Lamellipodium formation is not required for the formation of a hemostatic plug or thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 40 publications
6
56
0
Order By: Relevance
“…6b) and adherent platelets formed prominent filopodia (Fig. 6b), confirming previous observations 31 . Time-lapse video microscopy, however, revealed premature lamellipodia-like extensions that protrude and retract between adjacent filopodia, but do not extend to filopodial tips (Supplementary Movie 6); and mean projected platelet area was significantly larger compared to Arpc2−/− platelets ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…6b) and adherent platelets formed prominent filopodia (Fig. 6b), confirming previous observations 31 . Time-lapse video microscopy, however, revealed premature lamellipodia-like extensions that protrude and retract between adjacent filopodia, but do not extend to filopodial tips (Supplementary Movie 6); and mean projected platelet area was significantly larger compared to Arpc2−/− platelets ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…6a). Previous reports have shown that WAVE rather than WASp is required for lamellipodia formation in platelets 31,44 . Indeed, spreading area of platelets isolated from conditional Pf4cre+/− Cyfip1fl/fl (Cyfip1−/−) mice was largely reduced compared to controls ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This was surprising, but we cannot exclude at present that-as opposed to DCs or macrophagesplatelets might be capable of expressing low amounts of the mostly non-hematopoietic Hem1 orthologue Nap1, allowing for WRC-driven Arp2/3 complex activation in a fashion indistinguishable from Hem1. Interestingly, platelets conditionally deleted for Cyfip1 but still harboring the intact gene for Cyfip2 display related but less severe phenotypes with aberrant morphology and reduced activatability (89), potentially due to residual WRC function. Likewise, when generating mouse melanoma cells CRISPR/Cas9-edited for Nap1, we isolated clones with differential but low levels of compensatory Hem1-expression, giving rise to significant levels of lamellipodia formation (48).…”
Section: Fc Gamma Receptor (Fc R)-induced Phagocytosis Is Mainly Accomentioning
confidence: 99%